1991
DOI: 10.1111/j.1600-0536.1991.tb01772.x
|View full text |Cite
|
Sign up to set email alerts
|

Type IV allergy to amide‐type local anesthetics

Abstract: The case of a 45-year-old woman is reported, who developed intense erythema and itching 1 day after subcutaneous (s.c.) injection of a local anesthetic containing mepivacaine and methylparaben. The reaction was attributed to a delayed-type sensitivity to mepivacaine, since mepivacaine gave a positive patch test response and also elicited a delayed sensitivity reaction after s.c. challenges, whereas prick and patch tests with methylparaben, as well as oral challenges, were negative. Interestingly, the patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…This decrease may be explained by the use of amide anesthetics (lidocaine, mepivacaine, bupivacaine, etc. ), which are less common sensitizers (30). Although we observed a decrease in positive reactions to benzocaine, our rate of benzocaine sensitization (B2%) remained higher compared with Sertoli and colleagues' and Shireen's studies, which found approximately 1.3% and 0.4%, respectively, of benzocaine positive reactions (15,31).…”
Section: Anestheticsmentioning
confidence: 40%
“…This decrease may be explained by the use of amide anesthetics (lidocaine, mepivacaine, bupivacaine, etc. ), which are less common sensitizers (30). Although we observed a decrease in positive reactions to benzocaine, our rate of benzocaine sensitization (B2%) remained higher compared with Sertoli and colleagues' and Shireen's studies, which found approximately 1.3% and 0.4%, respectively, of benzocaine positive reactions (15,31).…”
Section: Anestheticsmentioning
confidence: 40%
“…23 Adding more confusion to the scenario is the possibility of cross-sensitization. Klein et al 24 reported a patient who had a delayed-type reaction to mepivacaine. Patch testing results were positive for lidocaine and mepivacaine sensitivities, but the lidocaine patch revealed a more exuberant reaction.…”
Section: Patch Test Clinic Patientsmentioning
confidence: 99%
“…The patient's medical history was notable for exposure to lidocaine. 24 Our first patient reported a medical history positive for a pruritic rash days after an injection of local anesthetic for both dental surgery and breast biopsy. Her patch test result to lidocaine was strongly positive, and intradermal injection also revealed a pink papular eruption consistent with a delayed-type hypersensitivity reaction.…”
Section: Patch Test Clinic Patientsmentioning
confidence: 99%
“…This report was followed by others [15, 16]. Contact allergy to amide anesthetics is rare and, according to Klein and Gall [17] in 1991, only 18 cases had been reported since these medications began to be used in the 1940s. Most of the delayed-type hypersensitivity reactions take place after a topical application of the drug [18].…”
Section: Discussionmentioning
confidence: 79%